Reasons for Gambling in University Students, Loneliness? A study on sports science students - Cuneyt Seydioglu; İhsan Yağcı; Umut Davut Başoğlu (Atatürk University, 2024)
This study was conducted to investigate the reasons behind university students' gambling and especially to examine the relationship between loneliness and gambling. The population of the research consists of the students of the Faculty of Sports Sciences in Istanbul. The sample consisted of 1051 volunteer students of the Faculty of Sports Sciences selected by random method. The study data were obtained through Personal Information Form, Reasons for Gambling Scale and UCLA Loneliness Scale. The sample group of the study consisted of students from 5 private and 2 foundation universities with a Faculty of Sports Sciences who had played at least one of the online games, sports betting, horse racing, lottery, card/table games and numerical lotto games with money in the last 3 months. The data obtained were analyzed using SPSS 25.0 package programme and the significance level was set as 0.05. According to the findings obtained as a result of the study, it was determined that students studying at private universities need to gamble for the reason of earning money, while students studying at public universities have a high urge to have fun/excitement as a reason for gambling. In addition, it was determined that students who do not work need to gamble for the reason of earning money. As another result, it was determined that students who do not do sports as a licensed athlete feel themselves more lonely than licensed athletes. In line with the main purpose of the study, it was concluded that loneliness triggers the urge to gamble.